Protective effects of voltage-gated calcium channel antagonists against zinc toxicity in SN56 neuroblastoma cholinergic cells - Zyśk, Marlena (PLoS One, 2018)
One of the pathological site effects in excitotoxic activation is Zn(2+) overload to postsynaptic neurons. Such an effect is considered to be equivalent to the glutamate component of excitotoxicity. Excessive uptake of Zn(2+) by active voltage-dependent transport systems in these neurons may lead to significant neurotoxicity. The aim of this study was to investigate whether and which antagonists of the voltage gated calcium channels (VGCC) might modify this Zn(2+)-induced neurotoxicity in neuronal cells. Our data demonstrates that depolarized SN56 neuronal cells may take up large amounts of Zn(2+) and store these in cytoplasmic and mitochondrial sub-fractions. The mitochondrial Zn(2+) excess suppressed pyruvate uptake and oxidation. Such suppression was caused by inhibition of pyruvate dehydrogenase complex, aconitase and NADP-isocitrate dehydrogenase activities, resulting in the yielding of acetyl-CoA and ATP shortages. Moreover, incoming Zn(2+) increased both oxidized glutathione and malondialdehyde levels, known parameters of oxidative stress. In depolarized SN56 cells, nifedipine treatment (L-type VGCC antagonist) reduced Zn(2+) uptake and oxidative stress. The treatment applied prevented the activities of PDHC, aconitase and NADP-IDH enzymes, and also yielded the maintenance of acetyl-CoA and ATP levels. Apart from suppression of oxidative stress, N- and P/Q-type VGCCs presented a similar, but weaker protective influence. In conclusion, our data shows that in the course of excitotoxity, impairment to calcium homeostasis is tightly linked with an excessive neuronal Zn(2+) uptake. Hence, the VGCCs types L, N and P/Q share responsibility for neuronal Zn(2+) overload followed by significant energy-dependent neurotoxicity. Moreover, Zn(2+) affects the target tricarboxylic acid cycle enzymes, yields acetyl-CoA and energy deficits as well.